Damage analysis of ship collisions with offshore wind turbine foundations - Moulas, D.; Shafiee, M.; Mehmanparast, A. (Ocean engineering, 2017)
Nowadays, a large number of wind turbines are being installed offshore due to more stable and steady flow of wind at sea and also less noise and visual impact compared to onshore wind farms. With the growing number of offshore wind installations, particular attention should be paid to the safe operation of assets. Offshore wind assets are subject to extreme environmental conditions and high dynamic stresses caused by wind, waves and currents. More importantly, they are largely exposed to hazards associated with collision with either commercial ships or infield support vessels passing closely at high speeds. To date, the damage analysis of collisions between infield support vessels and offshore wind turbine foundations has received very limited attention. In this study, a numerical nonlinear finite element analysis (NLFEA) approach is developed to evaluate the damage to wind turbine foundations when stricken by an offshore support vessel. The model is applied to a case study where 4000 tons class vessels collide with two common types of fixed-bottom foundations, namely monopile and jacket structure in shallow and deep waters respectively. Various accident scenarios are identified and the resulting damage to wind turbine foundations are analyzed. The number, location and the extent of damage to the members in each scenario are determined and the effects of reinforcement on the structure response are evaluated. The results of this research provide a good understanding of the factors that affect magnitude of damage caused by ship-wind turbine collision accidents and give an insight on how the next generation of wind turbine foundations can be designed in a more “collision-friendly” way. •A nonlinear finite element analysis (NLFEA) approach to evaluate the damage to offshore wind foundations stricken by infield vessels.•To identify various collision scenarios and analyzing the damage to wind turbine foundations.•To determine the number, location and the extent of damage to the members in each scenario.•A case study to simulate the collision of 4000 tons class vessels with monopile foundations and jacket structures.•To evaluate the effect of reinforcing the structure on ship collision damages.